Comparative analysis of green inhibitors vs. inhibitors traditional in metal corrosion - Agraje, Zariyen (2020)
The most widely used industrial inhibitors to decrease corrosion are those that contain heteroatoms (such as N, S, P, O), causing damage to the environment, which is why natural alternatives have been chosen. Green inhibitors are a friendly alternative for the environment, since they allow us to reduce certain problems that are affecting our planet, through the excessive use of chemical products. This research involves comparing green fruit-based inhibitors versus traditional inhibitors. The design of this study is experimental, with three treatments and one control. Treatments consisted of three types of green inhibitors and one inhibitor for industrial use. The green inhibitors were prepared respectively with the following natural materials: avocado pulp, extract of the green apple peel and pulp of the green apple. With these 3 types of green inhibitors, it was possible to study the levels of corrosion in metals, through the weight loss presented in A36 carbon steel sheets. These metal plates were exposed to a marine environment and to a controlled laboratory environment. At the end of our investigation, we could see that the green inhibitor based on the avocado pulp was the most effective, since it could more efficiently counteract the corrosion rate in the metal plates. Although, they do not have a percentage of effectiveness as the industrial inhibitor, but it can be used as an alternative to mitigate the corrosion process.